Ecological quality standards for drinking and surface waters in Ukraine and Poland - Rychak , N. L.; Yefremova, A. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2025)
Purpose. Analysis of the regulatory framework, assessment of qualitative and quantitative indicators of drinking water and surface waters in Ukraine and Poland.Methods. Comparative legal methodResults. Based on a comparison of real standards and approaches to monitoring in both countries, based not only on theoretical sources, but also on a practical comparison of digital indicators, it was determined for the drinking waters of the countries: regulatory requirements for organoleptic indicators differ in the permissible limits of the intensity of these characteristics and methodological approaches to their determination; in Poland, the issue of bacteriological water safety is more standardized; drinking water quality standards in Ukraine and Poland are very close, but Poland in many cases sets stricter requirements for individual indicators (especially iron, manganese, ammonium). For organoleptic indicators of surface water quality in Ukraine, the standards are more specific and quantitative. For physicochemical indicators of surface water quality, significant differences are revealed.Conclusions. Poland has fully integrated the requirements of the European Union Directives into its legislation, while in Ukraine this process is still ongoing. Further harmonization of Ukrainian environmental standards with European requirements is necessary, which is in line with the provisions of the State Policy Strategy of Ukraine and the goals of sustainable development.